(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
This article discusses the definition and implementation of management decision-making procedures in integrated management-based systems. In the process of intellectual support of decision-making, the determination of efficiency characteristics through a mathematical model was carried out by selecting unwanted parameters in the management system. It has also been shown that an algorithm based on a two-stage nonlinear model allows management decisions to be made. In assessing the sources of incoming information, an unambiguous model was used in the optimal organization of the process according to the decision support mechanism based on the conclusions of expert systems. According to the MATLAB application package, the research indicators were carried out experimentally.